Loan Sales and the Cost of Corporate Borrowing - Güner, A. Burak (Review of Financial Studies, 2006)
When a loan is sold, it goes to a lower-cost financing source than its originator. Yet, lending markets are less than perfectly competitive. Despite the lower funding cost, therefore, the loan price is not necessarily more favorable to the borrower. However, corporate borrowers are averse to the participation of their loans to other lenders because of the complexity of dealing with multiple banks and the potential information costs of the sale announcement. Consequently, I conjecture that the borrower extracts a price concession in exchange for allowing the bank to sell participations in the loan. Using a hand-matched dataset of loans, borrowers, and lenders, I find that the average yield spread on loans originated by active loan sellers is about 20 basis points lower than the average spread on loans originated by moderate loan sellers. Copyright 2006, Oxford University Press.